Discordance Between Resting and Hyperemic Indices of Coronary Stenosis Severity: The VERIFY 2 Study (A Comparative Study of Resting Coronary Pressure Gradient, Instantaneous Wave-Free Ratio and Fractional Flow Reserve in an Unselected Population Referred for Invasive Angiography). (November 2016) - Hennigan, Barry; Oldroyd, Keith G.; Berry, Colin; Johnson, Nils; McClure, John; McCartney, Peter; McEntegart, Margaret B.; Eteiba, Hany; Petrie, Mark C.; Rocchiccioli, Paul; Good, Richard; Lindsay, Martin M.; et al.
Abstract : Background—: Distal coronary to aortic pressure ratio (Pd/Pa) and instantaneous wave-free ratio (iFR) are indices of functional significance of a coronary stenosis measured without hyperemia. It has been suggested that iFR has superior diagnostic accuracy to Pd/Pa when compared with fractional flow reserve (FFR). We hypothesized that in comparison with FFR, revascularization decisions based on either binary cutoff values for iFR and Pd/Pa or hybrid strategies incorporating iFR or Pd/Pa will result in similar levels of disagreement. Methods and Results—: This is a prospective study in consecutive patients undergoing FFR for clinical indications using proprietary software to calculate iFR. We measured Pd/Pa, iFR, FFR, and hyperemic iFR. Diagnostic accuracy versus FFR ⩽0.80 was calculated using binary cutoff values of ⩽0.90 for iFR and ⩽0.92 for Pd/Pa, and adenosine zones for iFR of 0.86 to 0.93 and Pd/Pa of 0.87 to 0.94 in the hybrid strategy. One hundred ninety-seven patients with 257 stenoses (mean diameter stenosis 48%) were studied. Using binary cutoffs, diagnostic accuracy was similar for iFR and resting Pd/Pa with misclassification rates of 21% versus 20.2% ( P =0.85). In the hybrid analysis, 54% of iFR cases and 53% of Pd/Pa cases were outside the adenosine zone and rates of misclassification were 9.4% versus 11.9% ( P =0.55). Conclusions—: Binary cutoff values for iFR and Pd/Pa result in misclassification of 1 in 5 lesions. Using a hybrid strategy, approximately half of the patients do not receive adenosine, but 1 in 10 lesions are still misclassified. The use of nonhyperemic indices of stenosis severity cannot be recommended for decision making in the catheterization laboratory. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02377310.